'How does it look and feel to be plurilingual?': analysing children's representations of plurilingualism through collage. Issue 8 (13th September 2020) - Prasad, Gail
ABSTRACT: Linguistic diversity has become a defining feature of schools in the twenty-first century. How do children make sense of such diversity and their own linguistic identities? This article draws on data generated through a multi-site inquiry with five English and French schools in Canada and France to investigate children's plurilingualism. According to educational policy and curriculum in each context, all of the children involved in this study were receiving instruction at school in English and French. In addition, many children spoke other languages outside of school, at home and in their communities. At the conclusion of each 4–6 month research collaboration in each school, children engaged in making collages that responded to the question, 'How does it look and feel to be plurilingual'? Drawing on social theories of language representation and plurilingualism, the focus herein is on analyzing how children's representations of plurilingualism made visible through the medium of collage. This article argues for the usefulness of creative multimodal arts-based methods in applied linguistics research and in particular for engaging plurilingual children as co- investigators.